Livelihood Improvement through Entrepreneur Characteristics and Innovative Strategies: An Empirical Study of Entrepreneurs in Western Kenya - Nassiuma, Bernard Kibeti; Chebii, Pamela; Masinde, Jamin; Sergon, David (Advances in Social Sciences Research Journal, 2021)
Purpose This study aimed at improving an understanding of the mediating role of innovation in the relationship between entrepreneur characteristics and livelihood improvement. The study was empirical, based on primary data from the micro and small enterprises in the western region of Kenya. Design/methodology study adopted a quantitative approach, self-administered questionnaires were used to gather data from 382 Micro and Small Enterprises (MSEs) owners in Western Kenya, comprising Uasin Gishu and Bungoma Counties. The study examined the direct and indirect effects on livelihood improvement. A simple random sampling technique was used to select respondents for data collection. For statistical analysis, bivariate regression and multiple regression techniques were utilized with SPSS version 26 being the tool. The sopel test assisted in analyzing the effect of innovation as a mediator between entrepreneur characteristics and livelihood improvement. FindingsThe results reveal a statistically significant relationship between the entrepreneur characteristics and livelihood improvement under the mediating role of innovation. Practical implications these findings provide useful insights for MSEs, seeking to be competitive and responsive to the changing entrepreneurial landscape by successfully introducing innovations. The study encourages an innovative culture among the MSEs owners which is likely to facilitate the introduction, adoption, and diffusion of innovations that can in turn, result in the achievement of livelihood improvement. Originality/valueThe study contributes to the existing literature by enhancing an understanding of the mediating role of innovation in the relationship between entrepreneur characteristics and livelihood improvement in the MSEs sector of a developing context. Keywords: MSEs, innovation, mediation, entrepreneur characteristics, improved livelihood, western Kenya.